Enhanced‐efficiency nitrogen fertilizers reduce winter losses of nitrous oxide, but not of ammonia, from no‐till soil in a subtropical agroecosystem. (8th February 2020) - Ribeiro, Ricardo Henrique; Besen, Marcos Renan; Simon, Priscila Luzia; Bayer, Cimelio; Piva, Jonatas Thiago
Abstract: Nitrogen (N) gas losses can be reduced by using enhanced‐efficiency N (EEN) fertilizers such as urease inhibitors and coating technologies. In this work, we assessed the potential of EEN fertilizers to reduce winter losses of nitrous oxide (N2 O‐N) and ammonia (NH3 ‐N) from a subtropical field experiment on a clayey Inceptisol under no‐till in Southern Brazil. The EEN sources used included urea containing N ‐( n ‐butyl) thiophosphoric triamide (UR+NBPT), polymer‐coated urea (P‐CU) and copper‐and‐boron‐coated urea (CuB‐CU) in addition to common urea (UR) and a control treatment without N fertilizer application. N2 O‐N and NH3 ‐N losses were assessed by using the static chamber method and semi‐open static collectors, respectively. Both N2 O‐N and NH3 ‐N exhibited two large peaks with an intervening period of low soil moisture and air temperature. Although the short‐term effect was limited to the first few days after application, UR + NBPT urea decreased soil N2 O‐N emissions by 38% relative to UR. In contrast, urease inhibitor technology had no effect on NH3 ‐N volatilization. Both coating technologies (CuB‐CU and P‐CU) were ineffective in reducing N losses via N2 O production or NH3 volatilization. The N2 O emission factor (% N applied released as N2 O) was unaffected by all N sources and amounted to only 0.48% of N applied—roughly one‐half the default factor of IPCC Tier 1 (1%). Based on our findings, using NBPT‐treated urea in the cold winter season in subtropical agroecosystems provides environmental benefits in the form of reduced soil N2 O emissions; however, fertilizer coating technologies provide no agronomic (NH3 ) or environmental (N2 O) advantages.